Diversity and traditional knowledge of medicinal plants in home gardens of Kampung Masjid Ijok, Perak, Malaysia - Mohd Raznan Ramli; POZI MILOW; SORAYYA MALEK (Society for Indonesian Biodiversity, 2021)
Abstract. Ramli MR, Milow P, Malek S. 2021. Diversity and traditional knowledge of medicinal plants in home gardens of Kampung Masjid Ijok, Perak, Malaysia. Biodiversitas 22: 2458-2465. Medicinal plants and associated traditional knowledge are at risk of habitat modification, globalization, urbanization, and modernization. Though home gardens are recognized as a potential strategy for medicinal plant conservation, at the same time very limited efforts have been made for the documentation of ethnomedicinal plants. We explored and documented the diversity and population status of ethnomedicinal plants in the home gardens of Kampung Masjid Ijok along with its associated traditional knowledge. Field observation and semi-structured interviews were conducted to record for the medicinal uses of the medicinal plants in the home gardens. The information, i.e. local name, parts used, methods of preparation, and type of ailments, were also collected. The total numbers of medicinal plants recorded in the study area were 68 species belonging to 40 families. The families of Zingiberaceae, Asteraceae, Acanthaceae, and Fabaceae were recorded as having the highest number of medicinal plants. Herbs were the main source of medicinal plants in terms of species number followed by shrubs, trees, and climbers. Cocos nucifera L, Carica papaya L, Areca catechu L, and Citrus aurantiifolia (Chris. & Panz.) Swin were the most frequent species of medicinal plants. Shannon diversity index of medicinal plant species was 3.7. The most frequently utilized plant parts were the leaves followed by roots, fruits, rhizomes, whole plants, flowers, seeds, and barks. Gastrointestinal disorders including stomach ache, diarrhea, dysentery, indigestion, flatulence, worm infestation in children, and constipation were among the most frequent ailments treated with the medicinal plants. This study revealed that many medicinal plants are still broadly found in home gardens and used for treating various ailments. The information recorded in this study may form the basis for the conservation and sustainable use of ethnomedicinal plants and may also contribute to the preservation of cultural and genetic diversity.